Boxholm tea party: Taxation and voter turnout in a mature democracy. (June 2021) - Broms, Rasmus
Abstract: The link between taxation and representation is generally considered foundational to the emergence of democratic governance. Nevertheless, the empirical relationship between taxation and the extent to which citizens actually exert representation by turning out to vote remains virtually unexplored. Using a panel of all Swedish municipalities from 1979 to 2018, I find that hikes in local tax rates are linked to increased municipal voter turnout. Accounting for a wide range of confounders, including turnout in concurrent parliamentary- and county elections, these results indicate an important untapped explanation for changes in turnout, while offering a rare explicit test of the taxation-representation argument drawn from a mature democracy.